2012
DOI: 10.1371/journal.pone.0044775
|View full text |Cite
|
Sign up to set email alerts
|

Are Patent Medicine Vendors Effective Agents in Malaria Control? Using Lot Quality Assurance Sampling to Assess Quality of Practice in Jigawa, Nigeria

Abstract: BackgroundPatent medicine vendors (PMV) provide antimalarial treatment and care throughout Sub-Saharan Africa, and can play an important role in the fight against malaria. Their close-to-client infrastructure could enable lifesaving artemisinin-based combination therapy (ACT) to reach patients in time. However, systematic assessments of drug sellers’ performance quality are crucial if their role is to be managed within the health system. Lot quality assurance sampling (LQAS) could be an efficient method to mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 31 publications
2
34
1
Order By: Relevance
“…In the future, RSS will randomly sample PHCCs and hospitals as a stratum and then randomly choose a PHCU in the catchment area for each selected PHCC, as was performed in Nigeria (Berendes et al . ). Another limitation was due to the low utilisation of many PHCUs, which rendered the clinical observation and exit interview modules difficult to carry out, as we had to exclude HFs if the misclassification error was ≤20% for both alpha and beta.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the future, RSS will randomly sample PHCCs and hospitals as a stratum and then randomly choose a PHCU in the catchment area for each selected PHCC, as was performed in Nigeria (Berendes et al . ). Another limitation was due to the low utilisation of many PHCUs, which rendered the clinical observation and exit interview modules difficult to carry out, as we had to exclude HFs if the misclassification error was ≤20% for both alpha and beta.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, we used LQAS for the rapid assessment of public and private HFs in Nigeria (Berendes et al . ; Oladele et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…The Ministry of Health (MOH) is responsible for providing operational supervision to the private sector to ensure compliance standards. However, enforcing these standards is difficult due to inadequate numbers of qualified personnel to carry out this task [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…They are authorized to sell over-the-counter drugs including common drugs such as pain killers, cough syrups, and antimalarials 10. Several studies have reported PPMVs as the most common source of malaria treatment in Nigeria 2,1114. They are also reported to offer treatment of childhood diarrhea9 as well as hypertension 15.…”
Section: Introductionmentioning
confidence: 99%